Analisis Geographically Weighted Panel Regression di bidang Infrastruktur, Sosial, Kesehatan, Kependudukan, dan Pendidikan terhadap Produk Domestik Regional Bruto di Nusa Tenggara Timur - diacahyawati Dia Cahya Wati; Ismi Rizqa Lina; Andini Setyo Anggraeni (ESTIMASI: Journal of Statistics and Its Application, 2023)
Gross Regional Domestic Product (GRDP) is an important indicator of economic growth in a region. The success of regional economic growth is said to be good if the GRDP in an area has a significant effect on that area. However, economic growth in East Nusa Tenggara (NTT) has not been optimal. This is caused by economic inequality in NTT which differs between districts/cities. Therefore, the aim of this research is to find out what factors influence GRDP in NTT using Geographically Weighted Panel Regression (GWPR). The data used is sourced from the Central Statistics Agency (BPS) website. The results of the study describe that GRDP in NTT is divided into 12 groups with the adaptive bisquare kernel function and the coefficient of determination is 83.73%. The independent factors that influence GRDP in NTT are the Construction Expensive Index (IKK) and Area Area (LW) in the construction sector, the Human Development Index (IPM) in the Social sector, the Number of Poor population in the population sector, and the Literacy Rate (AMH) in the education sector. Meanwhile, the health sector did not affect GRDP in NTT.